Characterization of the Leucistic Texas Rat Snake Pantherophis obsoletus - Ullate-Agote, Asier; Tzika, Athanasia C. (Frontiers in Ecology and Evolution, 2021)
Albinism and leucism are phenotypes resulting from impaired melanin pigmentation in the skin and skin appendages. However, melanin pigmentation of eyes remains unaffected in leucism. Here, using transmission electron microscopy, we show that the leucistic morph of the Texas rat snake (Pantherophis obsoletus lindheimeri) lacks both melanophores and xanthophores in its skin and exhibits a uniform ivory white color generated by iridophores and collagen fibers. In addition, we sequenced the full genome of a leucistic individual and obtained a highly-contiguous near-chromosome quality assembly of 1.69 Gb with an N50 of 14.5 Mb and an L50 of 29 sequences. Using a candidate-gene approach, we then identify in the leucistic genome a single-nucleotide deletion that generates a frameshift and a premature termination codon in the melanocyte inducing transcription factor (MITF) gene. This mutation shortens the translated protein from 574 to 286 amino acids, removing the helix-loop-helix DNA-binding domain that is highly conserved among vertebrates. Genotyping leucistic animals of independent lineages showed that not all leucistic individuals carry this single-nucleotide deletion. Subsequent gene expression analyses reveal that all leucistic individuals that we analysed exhibit a significantly decreased expression of MITF. We thus suggest that mutations affecting the regulation and, in some cases, the coding sequence of MITF, the former probably predating the latter, could be associated with the leucistic phenotype in Texas rat snakes. MITF is involved in the development and survival of melanophores in vertebrates. In zebrafish, a classical model species for pigmentation that undergoes metamorphosis, larvae and adults of homozygous mitfa mutants lack melanophores, show an excess of iridophores and exhibit reduced yellow pigmentation. On the contrary, in the leucistic Texas rat snake, a non-metamorphic species, only iridophores persist. Our results suggest that fate determination of neural-crest derived melanophores and xanthophores, but not of iridophores, could require the expression of MITF during snake embryonic development.